Model Pembelajaran Core untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar - amanda lembah muria; Yudi Budianti (Universitas Pendidikan Indonesia (UPI), 2021)
Science is one of the subjects given in elementary schools that examine natural events and everyday life, learning science is very important for elementary school students because in everyday life students need scientific background knowledge. This study aims to describe the increase in science learning outcomes in elementary schools through the implementation of the CORE learning model. One of the factors that influence success in learning is student activity. In the learning process students are required to be active through activities that build group work and in a short time make them think about the subject matter. Active involvement of students in learning natural sciences (IPA) is very necessary, so that what is learned will be more embedded in students' minds to improve science learning outcomes using the CORE Model (Connecting, Organizing, Reflecting, and Extending).